Assessment Of Perceived Causes and Levels of Stress Amongst Clinical Dental Students and House Surgeons. A Cross-Sectional Study - Aisha Wali Wali; Kashif Ikram; Talha Siddiqui; Rubab Jawed; Khaliq Dad Muhammadi; Mazid Ahmed; Abdul qudos (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objective: The aim of the study was to assess perceived causes and levels of stress amongst clinical dental students and house surgeons of Baqai Dental College. Methods:  A cross sectional study was conducted from October 2018 - December 2018 after getting ethical approval from ethical committee, Baqai Medical University and permission for data collection was approved from R&D department, Baqai Dental College. (BDC/ERB/2018/011) Dental students from third year, final year and house surgeons were included in the study (n= 250). A structured pre validated questionnaire DES questionnaire 21 consisted of 23 closed ended questions with three responses of categories that are 1) No stress, 2) Mild- moderate and 3) severe stress was used. Data was analysed for frequency and percentages and chi -square test was done to assess the association between academic qualifications with other variables. Results: The response rate was 59.2%. Majority of them were females 56.8% and 43.2% were male participants. Forty three (28.9%) of the participants reported severe stress regarding fear of getting infectious disease from patients. Thirteen (35.1%) of 3rd year BDS students reported stress regarding examination and grading of patient when compared to 4th year BDS students and house surgeons with a significant relationship. Seventeen (22.7%) of 4th year BDS students reported severe stress due to fear of failure in examination when compared to 3rd year BDS students and house surgeons. Thirteen (35.1%) of the 3rd year BDS students reported stress regarding difficulty with class work Conclusion: The outcomes of the concluded study are: • Maximum stress level was reported due to fear of getting infectious diseases from patients and fear of failure in examination. • Women reported maximum stress levels than men. • 3rd year BDS students reported severe stress than 4th year BDS students.